Insilico analysis of adenylation and ketosynthase domain related to antifungal activity of rice phyllosphere bacteria - Wiraswati, Sri Martina; Rusmana, Iman; Nawangsih, Abdjad Asih; Wahyudi, Aris Tri (Biogenesis: Jurnal Ilmiah Biologi, 2023)
.